High-performance die-cast aluminum-silicon alloy for automotive lightweight components and die-casting method

By combining specific component ratios and multi-stage high-pressure casting with high-frequency oscillating current treatment, the problems of coarse microstructure and defects in aluminum-silicon alloy casting have been solved, achieving simultaneous improvement in the alloy's strength and plasticity and simplification of the production process, making it suitable for lightweight automotive components.

CN121406948BActive Publication Date: 2026-03-20JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511996760.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-27
Publication Date
2026-03-20
Estimated Expiration
2045-12-27

AI Technical Summary

Technical Problem

Existing aluminum-silicon alloy casting processes suffer from microscopic segregation, porosity, and shrinkage defects caused by coarse dendritic structures, as well as problems such as multiphase hard and brittle phases cutting the matrix and gas entrainment into the mold cavity forming micropores. It is difficult to simultaneously achieve grain refinement, eutectic silicon modification, and refinement of acicular iron-containing and copper-containing phases, and it is also difficult to improve strength and plasticity at the same time.

Method used

An aluminum-silicon alloy with a specific composition ratio, including Si, Cu, Mg, Fe, Mn, Cr, B, and La, is used. Through multi-step high-pressure casting and high-frequency oscillating current treatment, the alloy composition and process parameters are synergistically controlled to achieve simultaneous refinement of α-Al grains, iron-containing phases, copper-containing phases, and eutectic silicon, thereby optimizing the microstructure.

Benefits of technology

It significantly improves the density and mechanical properties of the alloy, simultaneously enhancing yield strength, tensile strength, and elongation after fracture, simplifying the production process, reducing costs, extending mold life, and achieving a simultaneous improvement in the strength and plasticity of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121406948B_ABST
    Figure CN121406948B_ABST
Patent Text Reader

Abstract

The application provides a high-performance die-casting aluminum-silicon alloy and a die-casting method for automobile lightweight components, and belongs to the field of high-end alloy casting; the aluminum-silicon alloy is composed of the following components in percentage by mass: Si: 9.0-12.0 wt.%, Cu: 0.5-1.0 wt.%, Mg: 0.50-0.60 wt.%, Fe: 0.10-0.15 wt.%, Mn: 0.15-0.20 wt.%, Cr: 0.10-0.20 wt.%, B: 0.03-0.06 wt.%, La: 0.10-0.15 wt.%, unavoidable impurities: ≤0.1 wt.%, and the balance of Al; the preparation method comprises the following steps: aluminum-silicon alloy smelting, refining, degassing and impurity removal, multi-step high-pressure casting, and high-frequency, oscillation and secondary cycle current treatment; the cast aluminum-silicon alloy has a room-temperature yield strength of ≥200 MPa, a tensile strength of ≥300 MPa, and an elongation after fracture of ≥15%; the high strength and toughness of the cast aluminum-silicon alloy make it more suitable for key components such as automobile bodies, chassis and engine supports, and under the premise of ensuring structural safety and reliability, the components can be significantly lightened, which meets the global green and sustainable development trend of the automobile industry.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of high-end alloy casting, and particularly relates to a high-performance die-casting aluminum-silicon alloy for light-weight automobile components and a die-casting method. BACKGROUND

[0002] Aluminum-silicon alloy has been widely used in important fields such as aerospace, construction engineering and automobile industry due to its high specific strength, excellent casting performance, low thermal expansion coefficient and good corrosion resistance. In recent years, with the continuous upgrading of industrial manufacturing technology, die-casting products are rapidly developing towards light weight, large structure, complex shape and component function integration, which puts forward higher requirements on the metallurgical quality and comprehensive mechanical properties of aluminum-silicon alloy castings. At present, the casting aluminum-silicon alloy mainly faces the following challenges in practical application: first, the coarse dendritic structure easily intensifies microsegregation and promotes the formation of casting defects such as pores and shrinkage, thereby significantly reducing the overall density and service reliability of the castings; second, polygonal flake eutectic silicon phase, coarse needle-shaped iron-containing phase and copper-containing phase exist in the matrix as hard and brittle phases, which can seriously cut the continuity of the aluminum matrix and form local stress concentration areas, becoming the source of crack initiation, and adversely affecting the strength and plasticity of the alloy; third, in the traditional casting process, due to the casting conditions, the gas in the mold cavity is difficult to completely discharge and is easily entrained into the metal liquid to form micro-pores, which are enlarged during high-temperature heat treatment, resulting in the rejection of the parts, thereby limiting the possibility of further improving the strength of the alloy through heat treatment and the industrialized production of high-strength casting materials.

[0003] In order to solve the above technical problems, the prior art usually uses high-cost grain refiners and modifiers to effectively refine the grain structure, such as adding Ti, Sr, Sb and other precious elements to refine or modify the eutectic silicon, but the process flow is complicated, the cost is high, and the addition amount, activity, suitable temperature and effective period of the refiner need to be considered. At present, if a certain problem is solved, a specific component or process needs to be used, if multiple problems are solved, multiple components or processes need to be added, and there is still a lack of efficient, simple and economical technical solutions that can simultaneously achieve grain refinement, eutectic silicon modification and refinement of coarse needle-shaped iron-containing phase and copper-containing phase. In addition, when the strength of the alloy is improved, the plasticity will be reduced, or when the plasticity of the alloy is improved, the strength will be reduced, that is, it is difficult to simultaneously improve the strength and plasticity of the alloy. Therefore, under the background of the current manufacturing industry pursuing green, efficient and economic development in parallel, how to reduce the alloy addition cost, simplify the casting process, and systematically optimize the composition design of the cast aluminum-silicon alloy to simultaneously achieve grain refinement and the refinement of coarse needle-shaped iron-containing phase and copper-containing phase, eutectic silicon modification, and finally realize the simultaneous improvement of strength and plasticity and the coordinated breakthrough of process efficiency, has become a key technical problem that needs to be solved in the industrialized production of aluminum-silicon alloy. SUMMARY

[0004] In order to solve the above technical problems, the application provides a high-performance die-casting aluminum-silicon alloy for light-weight components of automobiles, which is composed of the following components in percentage by mass: Si: 9.0-12.0 wt.%, Cu: 0.5-1.0 wt.%, Mg: 0.50-0.60 wt.%, Fe: 0.10-0.15 wt.%, Mn: 0.15-0.20 wt.%, Cr: 0.10-0.20 wt.%, B: 0.03-0.06 wt.%, La: 0.10-0.15 wt.%, unavoidable impurities: ≤0.1 wt.%, and the balance of Al; and the preparation method of the aluminum-silicon alloy comprises the following steps:

[0005] (1) according to the proportion of alloy components, the Al-Si, Al-Mn, Al-Cr, Al-Fe, Al-Cu, Al-B and Al-La alloy raw materials are polished to remove surface stains and oil stains, and then heated at 200-250℃ for 5-10 min; then heated to 750-780℃ for smelting; after the alloy is melted, it is stirred uniformly, then cooled to 690-710℃, and then slagging is performed; then magnesium ingots are added, melted, stirred uniformly, and then placed for 5-10 min to obtain a mixed melt 1;

[0006] The Al-Si alloy is any one of Al-10Si, Al-15Si or Al-25Si alloy; the Al-Mn alloy is any one of Al-10Mn, Al-15Mn or Al-25Mn alloy; the Al-Cr alloy is any one of Al-10Cr, Al-15Cr or Al-25Cr alloy; the Al-Fe alloy is any one of Al-10Fe, Al-15Fe or Al-25Fe alloy; the Al-Cu alloy is any one of Al-10Cu, Al-20Cu, Al-30Cu or Al-50Cu alloy; the Al-B alloy is any one of Al-3B, Al-8B or Al-10B alloy; and the Al-La alloy is any one of Al-5La, Al-10La or Al-20La alloy;

[0007] (2) after the mixed melt 1 obtained in step (1) is heated to 720-750℃, slagging is performed, a refining agent is added, and then stirred for 3-5 min; then placed for 5-10 min, and then high-purity argon is introduced for 3-5 min for degassing and impurity removal refining treatment; then placed for 5-10 min after slagging, and then heated at 660-680℃ for 5-10 min to obtain a mixed melt 2; the refining agent is K2CO3 or MgCO3, and the content is 0.2-0.6 wt.% of the total mass of the mixed melt 2;

[0008] (3) Casting the mixed melt 2 obtained in step (2) into an iron mold preheated to 200-250°C, and then performing a multi-stage high-pressure casting process under vacuum, wherein the multi-stage high-pressure casting process comprises the following stages: in the first stage, pushing at a speed of 0.05-0.2 m / s under a pressure of 80-100 MPa; in the second stage, pushing at a speed of 0.5-1.5 m / s under a pressure of 100-120 MPa; in the third stage, pushing at a speed of 2-3 m / s under a pressure of 130-160 MPa; and in the fourth stage, pushing at a speed of 0.01-0.05 m / s under a pressure of 10-20 MPa; and then solidifying, demolding, and cooling after pressure maintaining at 5-10 MPa for 10-15 s, to obtain an alloy casting;

[0009] (4) Subjecting the alloy casting obtained in step (3) to high-frequency, oscillation, 5-10 cycles of current treatment, each cycle of current treatment being performed at a voltage of 10-20 V, a current density of 5×10 7 ~3×10 9 A / m 2 , a frequency of 20-30 Hz, a duty cycle of 30-50%, and a treatment time of 1-2 s, and then obtaining a high-performance die-cast aluminum-silicon alloy for automobile lightweight components after cooling to room temperature; the high-performance die-cast aluminum-silicon alloy for automobile lightweight components has the following microstructure and properties: containing Al 15 (Fe, Mn, Cr)3Si2 and Cu-containing phases, both having a size of 5-10 μm, α-Al grain size: 90-100 μm, eutectic silicon size: 1-5 μm; in terms of mechanical properties, the yield strength is ≥200 MPa, the tensile strength is ≥300 MPa, and the elongation after fracture is ≥15%.

[0010] Further, the aluminum-silicon alloy consists of the following components in terms of mass percentage: Si: 9.5-10.5 wt.%, Cu: 0.6-0.8 wt.%, Mg: 0.55-0.58 wt.%, Fe: 0.12-0.14 wt.%, Mn: 0.16-0.18 wt.%, Cr: 0.12-0.18 wt.%, B: 0.04-0.05 wt.%, La: 0.12-0.14 wt.%, unavoidable impurities: ≤0.05 wt.%, and the balance being Al.

[0011] Further, according to the alloy composition proportioning in step (1), the Al-Si, Al-Mn, Al-Cr, Al-Fe, Al-Cu, Al-B and Al-La alloy raw materials are polished to remove surface stains and oil stains, then heated at 220-240 DEG C for 6-8 min, then heated to 760-770 DEG C for melting, after the alloy is melted, stirred uniformly, then cooled to 695-700 DEG C, slagging, then magnesium ingot is added, melted, stirred uniformly, and then obtained is mixed melt 1 after standing for 6-8 min.

[0012] Further, the refining agent in step (2) is K2CO3 or MgCO3, and the content is 0.3-0.5wt.% of the total mass of the melt.

[0013] Further, the mixed melt 2 obtained in step (2) is cast into an iron mold preheated at 220-240 DEG C, then subjected to multi-stage high-pressure casting treatment under vacuum, the multi-stage high-pressure casting treatment is as follows: in the first stage, the pushing speed is 0.1-0.15 m / s under a pressure of 85-95 MPa; in the second stage, the pushing speed is 0.8-1.2 m / s under a pressure of 105-115 MPa; in the third stage, the pushing speed is 2.2-2.5 m / s under a pressure of 140-150 MPa; in the fourth stage, the pushing speed is 0.02-0.04 m / s under a pressure of 12-15 MPa; after the pressure is maintained at 5-10 MPa for 12-14 s, the casting is solidified, demolded and cooled to obtain the alloy casting.

[0014] Further, the alloy casting in step (4) is subjected to high-frequency, oscillation, 6-8 times of cycle current treatment, and each current treatment is as follows: voltage 15-18 V; current density 8x10 7 ~2x10 9 A / m 2 ; frequency 22-28 Hz; the high-performance die-cast aluminum silicon alloy of the automobile lightweight component has the following structure and properties: containing Al 15 (Fe, Mn, Cr)3Si2 and Cu-containing phase, the size of both is 6-8 μm, the size of alpha-Al grain is 92-98 μm, and the size of eutectic silicon is 2-4 μm; in terms of mechanical properties, the yield strength is ≥ 210 MPa, the tensile strength is ≥ 320 MPa, and the elongation after fracture is ≥ 16%.

[0015] Compared with the prior art, the present application has the following advantages:

[0016] (1) The present application realizes the synergistic refinement of various organizations of the alloy through the synergistic design of multiple elements, precise component control, and the synergistic regulation of process and process parameters. In the existing process, the alloy organization is generally coarse, and it is difficult to simultaneously refine each component phase, microstructure and eutectic silicon morphology. If a certain problem is solved, a specific component or a certain process needs to be used. If multiple problems are solved, multiple components or multiple processes need to be added. For example, although the addition of Ti type refiner can refine the grain, it has no refining effect on other coarse organizations. The addition of Sr or Sb elements can improve the morphology of eutectic silicon, but cannot refine other phases. The present application can realize the synchronous refinement of alpha-Al grain, iron-containing phase, copper-containing phase and eutectic silicon phase and the optimization of their morphology, so that the size of alpha-Al grain is reduced from 1000-1500 μm to 90-100 μm, the eutectic silicon is converted from a long strip of 50-80 μm to a small point of 1-5 μm, the coarse Cu-containing phase (such as Al2Cu, Al5Mg8Si6Cu2) with a length of about 50-100 μm is converted into a small particle of 5-10 μm, and the coarse needle-shaped Al9Fe2Si2 phase with a length of about 100-200 μm is converted into Al 15 (Fe, Mn, Cr)3Si2 dispersed phase with a size of about 5-10 μm, fully embodying the systematicness and synergistic effect of component design, process and process parameters; omitting the complex process of adding refiners and modifiers in the prior art, solving the problem of process instability caused by the failure, degradation or reaction of additives with other elements; effectively reducing the fragmentation and stress concentration effects of iron-containing and copper-containing phases on the aluminum matrix. In summary, the alloy design of the present application does not need to rely on external grain refiners and modifiers and complex multi-step processes. Through the synergistic regulation of alloy internal component interaction, ratio, process and process parameters, the overall refinement of multiple phase organizations is realized, which not only simplifies the production process, reduces the cost, but also improves the strength, plasticity and stability of the alloy.

[0017] (2) The present application avoids the generation of turbulence during pouring to avoid the entrainment of gas, the difficulty in implementing heat treatment due to the entrained pores, the formation of shrinkage and porosity, the aggravation of mold wear (the mold life is prolonged by 20%), and the optimization of the melt filling process, realizes smooth filling of the runner, effectively reduces the gas entrainment phenomenon, orderly fills the cavity, ensures rapid filling of the cavity, and significantly reduces the tendency of shrinkage and porosity; compared with the prior art, the density of the high-performance die-casting aluminum-silicon alloy used for automobile lightweight components is increased by 10% or more, and the product yield is increased by 20% or more, which balances the forming quality and the economy of mold use.

[0018] (3) The present application utilizes the synergistic effect of thermal effect (Joule heat) and non-thermal effect (electron wind force), breaks through the limitation of classical diffusion kinetics, realizes vacancy-mediated diffusion acceleration and efficient nucleation of precipitates, solves the difficulty of heat treatment of die castings, has the advantages of no pollution, flexible operation, low equipment investment and remarkable treatment effect, promotes the high-density nucleation and rapid precipitation of strengthening phase, realizes the direct aging strengthening of as-cast structure, effectively avoids the pore expansion caused by traditional solid solution treatment, breaks the technical bottleneck of difficult realization of synchronous improvement of strength and plasticity of aluminum-silicon alloy in the prior art (i.e. strength increases, plasticity decreases; strength decreases, plasticity increases), provides a new technical path for synchronous improvement of strength and plasticity of die cast aluminum-silicon alloy, and simultaneously improves the strength and plasticity of the alloy: yield strength ≥ 200 MPa (increased by ≥ 26% compared with the prior art), tensile strength ≥ 300 MPa (increased by ≥ 20% compared with the prior art), and elongation after fracture ≥ 15% (increased by ≥ 82% compared with the prior art). BRIEF DESCRIPTION OF DRAWINGS

[0019] Figure 1 SEM image of high-performance die cast aluminum-silicon alloy 1 of the automobile lightweight component obtained in Example 1;

[0020] Figure 2 SEM image of high-performance die cast aluminum-silicon alloy 2 of the automobile lightweight component obtained in Example 2;

[0021] Figure 3 SEM image of high-performance die cast aluminum-silicon alloy 3 of the automobile lightweight component obtained in Example 3;

[0022] Figure 4 SEM image of die cast aluminum-silicon alloy casting obtained in Comparative Example 1. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical scheme and effect of the present application more clear and explicit, the following embodiments are used to further illustrate the present application, and it should be understood that the specific embodiments described herein are only used to explain the present application and do not limit the present application. The alloy performance obtained in Examples 1-3 and Comparative Example 1 is shown in Table 1.

[0024] Example 1:

[0025] The high-performance die cast aluminum-silicon alloy 1 of the automobile lightweight component is composed of the following components in mass percentage: Si: 9.5 wt.%, Cu: 0.6 wt.%, Mg: 0.52 wt.%, Fe: 0.12 wt.%, Mn: 0.20 wt.%, Cr: 0.15 wt.%, B: 0.04 wt.%, La: 0.12 wt.%, unavoidable impurity content ≤ 0.1 wt.%, and the balance is Al; the preparation method comprises the following steps:

[0026] (1) According to the proportion of alloy ingredients, the Al-Si, Al-Mn, Al-Cr, Al-Cu, Al-B and Al-La alloy raw materials are polished to remove surface stains and oil stains, preheated to 200°C for drying, and the surface moisture of the alloy is removed. The dried metal raw materials are heated to 750°C for smelting. After the intermediate alloy is melted, it is stirred uniformly, and then the temperature is reduced to 690°C. The magnesium ingot is pressed below the liquid surface. After the mixture is melted and stirred uniformly, it is left for 5 min to obtain a mixed melt 1;

[0027] (2) Then the mixed melt 1 obtained in step (1) is heated to 720°C, and then K2CO3 refining agent is pressed to the bottom of the mixed melt 1 with a pressure cover, stirred for 3 min, left for 5 min, and then high-purity argon is introduced into the mixed melt 1 for 3 min for degassing and impurity removal refining treatment. After slagging, it is left for 5 min and heated to 670°C to obtain a mixed melt 2;

[0028] (3) The iron mold is preheated to 210°C, and then the mixed melt 2 obtained in step (2) is cast into the mold. The vacuum system is vacuumed (vacuum degree 5 kPa), and multi-stage high-pressure casting treatment is carried out. First stage: advance at a speed of 0.05 m / s under a pressure of 80 Pa; second stage: advance at a speed of 0.5 m / s under a pressure of 100 MPa; third stage: advance at a speed of 2 m / s under a pressure of 130 MPa; fourth stage: advance at a speed of 0.01 m / s under a pressure of 10 MPa for feeding; after 10 s of pressure holding at 5 MPa, solidification, demolding and cooling are carried out to obtain an alloy casting;

[0029] (4) The graphite electrode is tightly attached to both sides of the alloy casting obtained in step 3, and then high-frequency, oscillation, and circulating current treatment is carried out for 10 times. Each current treatment: voltage 12V; current density 6×10 7 A / m 2 ; frequency 20Hz; duty cycle 30% process parameters for 1s. After the sample returns to room temperature, a high-performance die-casting aluminum silicon alloy 1 for automobile lightweight components is obtained. As shown in Figure 1 , the Fe-containing phase is dispersedly distributed with a size of about 5μm; the Cu-containing phase is transformed into a fine granular shape with a size of about 5μm; the α-Al grain size is significantly refined to about 90μm; and the eutectic silicon phase is optimized from a coarse strip shape to a point shape with a size of about 2μm. The optimization of the microstructure significantly improves the final mechanical properties of the high-performance die-casting aluminum silicon alloy 1 for automobile lightweight components: the yield strength reaches about 200MPa, the tensile strength is about 310MPa, and the elongation after fracture is 15.8%.

[0030] Example 2:

[0031] High-performance die-casting aluminum-silicon alloy 2 for automobile lightweight components consists of the following mass percentages of components: Si: 10 wt.%, Cu: 0.75 wt.%, Mg: 0.55 wt.%, Fe: 0.11 wt.%, Mn: 0.15 wt.%, Cr: 0.12 wt.%, B: 0.06 wt.%, La: 0.15 wt.%, unavoidable impurity content ≤0.1 wt.%, and the balance of Al; the preparation method comprises the following steps:

[0032] (1) According to the proportion of alloy components, the Al-Si, Al-Mn, Al-Cr, Al-Cu, Al-B, and Al-La alloy raw materials are polished to remove surface stains and oil stains, and then dried at a preheating temperature of 200°C to remove water on the surface of the alloy. The dried metal raw materials are heated to 780°C for smelting. After the intermediate alloy is melted, it is stirred uniformly, and then the temperature is reduced to 700°C. The magnesium ingot is pressed below the liquid surface. After the mixture is melted and stirred uniformly, it is allowed to stand for 10 min to obtain a mixed melt 1;

[0033] (2) Then, the mixed melt 1 obtained in step (1) is heated to 750°C, and then the MgCO3 refining agent is pressed into the bottom of the mixed melt 1 using a pressing cover. After stirring for 5 min, the mixed melt 1 is allowed to stand for 10 min. High-purity argon gas is then introduced into the mixed melt 1 for 5 min for degassing and impurity removal refining treatment. After slagging, the mixed melt 1 is allowed to stand for another 10 min and is kept at a temperature of 680°C to obtain a mixed melt 2;

[0034] (3) The iron mold is preheated to 210°C, and then the mixed melt 2 obtained in step (2) is poured into the mold. A vacuum system is used to create a vacuum (vacuum degree of 10 kPa) for multi-step high-pressure casting treatment. In the first stage, the mixed melt 2 is pushed at a speed of 0.1 m / s under a pressure of 90 MPa. In the second stage, the mixed melt 2 is pushed at a speed of 1.0 m / s under a pressure of 110 MPa. In the third stage, the mixed melt 2 is pushed at a speed of 2.5 m / s under a pressure of 145 MPa. In the fourth stage, the mixed melt 2 is pushed at a speed of 0.03 m / s under a pressure of 15 MPa for feeding. After 12 s of pressure maintenance at 10 MPa, the alloy casting is obtained after solidification, demolding, and cooling;

[0035] (4) The graphite electrode is tightly attached to both sides of the alloy casting obtained in step 3. Then, high-frequency, oscillation, and 8-cycle current treatment are performed. Each current treatment is performed at a voltage of 20 V, a current density of 8×10 8 A / m2, a frequency of 25 Hz, and a duty cycle of 40% for 1.2 s. After the sample returns to room temperature, the high-performance die-casting aluminum-silicon alloy 2 for automobile lightweight components is obtained.

[0036] The high-performance die-casting aluminum-silicon alloy 2 for automobile lightweight components, as obtained, has a yield strength of about 210 MPa, a tensile strength of about 321 MPa, and an elongation of about 16.5%. Figure 2 As shown, the Fe-containing phase is dispersedly distributed, with a size of about 7 μm; the Cu-containing phase is transformed into fine granular shape with a size of about 8 μm; the α-Al grain size is significantly refined to about 100 μm; and the eutectic silicon phase is optimized from coarse long strip shape to about 5 μm of point shape. The optimization of the microstructure significantly improves the final mechanical properties of the high-performance die-casting aluminum-silicon alloy 2 for automobile lightweight components: the yield strength reaches about 210 MPa, the tensile strength is about 321 MPa, and the elongation after fracture is 16.5%.

[0037] Example 3

[0038] The high-performance die-casting aluminum-silicon alloy 3 for automobile lightweight components is composed of the following components in mass percentage: Si: 12.0 wt.%, Cu: 1.0 wt.%, Mg: 0.60 wt.%, Fe: 0.15 wt.%, Mn: 0.20 wt.%, Cr: 0.20 wt.%, B: 0.06 wt.%, La: 0.12 wt.%, unavoidable impurity content ≤ 0.1 wt.%, and the balance of Al;

[0039] The preparation method of the aluminum-silicon alloy comprises the following steps:

[0040] (1) According to the alloy component proportion, the Al-Si, Al-Mn, Al-Cr, Al-Cu, Al-B and Al-La alloy raw materials are polished to remove surface stains and oil stains, and then dried at a preheating temperature of 200°C to remove the water on the surface of the alloy. The dried metal raw materials are heated to 750-780°C for smelting. After the intermediate alloy is melted, it is stirred uniformly, and then the temperature is reduced to 690-700°C, the magnesium ingot is pressed below the liquid surface, and after the mixture is melted and stirred uniformly, it is left to stand for 5-10 min to obtain a mixed melt 1;

[0041] (2) Then the mixed melt 1 obtained in step (1) is heated to 720-750°C, and then the MgCO3 refining agent is pressed into the bottom of the mixed melt 1 with a pressing cover, stirred for 3 min, left to stand for 8 min, and then high-purity argon is introduced into the mixed melt 1 for 4 min for degassing and impurity removal refining treatment. After the slag is removed, it is left to stand for 6 min, and then heated to 680°C to obtain a mixed melt 2;

[0042] (3) Preheat the iron mold to 250°C, and then pour the mixed melt 2 obtained in step (2) into the mold. Vacuum system is used to evacuate (vacuum degree 8 kPa) and perform multi-stage high pressure casting. First stage: under 100 MPa pressure, advance at a speed of 0.2 m / s; second stage: under 120 MPa pressure, advance at a speed of 1.5 m / s; third stage: under 160 MPa pressure, advance at a speed of 3 m / s; fourth stage: under 20 MPa pressure, advance at a speed of 0.05 m / s to complete the feeding; after holding at 10 MPa pressure for 15s, solidify, demold and cool to obtain alloy casting.

[0043] (4) Place the graphite electrode pairs tightly against both sides of the alloy casting obtained in step 3, and then perform high-frequency, oscillating, 5-cycle current treatment, with each current treatment having a voltage of 20V and a current density of 3×10⁻⁶. 9 A / m 2 The sample was processed for 2 seconds at a frequency of 28 Hz and a duty cycle of 50%. After the sample was restored to room temperature, a high-performance die-cast aluminum-silicon alloy 3 for lightweight automotive components was obtained.

[0044] In the obtained high-performance die-cast aluminum-silicon alloy 3 for lightweight automotive components, such as Figure 3 As shown, the Fe-containing phase is dispersed and has a size of approximately 8 μm; the Cu-containing phase transforms into fine particles of approximately 6 μm; the α-Al grain size is significantly refined to approximately 98 μm; and the eutectic silicon phase is optimized from coarse, elongated strips to a dot-like morphology of approximately 7 μm. This microstructure optimization significantly improves the final mechanical properties of the high-performance die-cast aluminum-silicon alloy 3 used for lightweight automotive components: the yield strength reaches approximately 200 MPa, the tensile strength is approximately 309 MPa, and the elongation after fracture reaches 15.6%.

[0045] Comparative Example 1

[0046] The die-cast aluminum-silicon alloy is composed of the following components by mass percentage: Si: 7.0 wt.%, Cu: 2 wt.%, Mg: 0.30 wt.%, Fe: 0.25 wt.%, Mn: 0.30 wt.%, Cr: 0.05 wt.%, B: 0.01 wt.%, La: 0.20 wt.%, with unavoidable impurities ≤0.1 wt.%, and the balance being Al; the preparation method includes the following steps:

[0047] (1) According to the alloy composition ratio, after grinding to remove surface stains and oil stains, Al-Si, Al-Mn and Al-Cu alloy raw materials are dried in a drying oven at a preheating temperature of 200℃ to remove surface moisture. The dried metal raw materials are placed in a preheated crucible in a resistance furnace and heated to 750℃. After the intermediate alloy melts, it is stirred evenly, and then the temperature is lowered to 690℃ to remove slag. The magnesium ingot is pressed below the liquid surface. After the mixture melts, it is stirred evenly and allowed to stand for 5~10 minutes to obtain mixed melt 1.

[0048] (2) Then, after heating the mixed melt 1 obtained in step (1) to 720°C, remove the slag, add Al-5Ti-1B refining agent to the mixed melt 1, stir evenly, let stand for 5~10 minutes, then add Sr-containing modifier, stir evenly, let stand for 5~10 minutes, then press MgCO3 refining agent to the bottom of the mixed melt 1 with a pressure hood, stir for 3~5 minutes, let stand for 5~10 minutes, then introduce high-purity argon into the mixed melt 1, continue for 3~5 minutes to degas and remove impurities for refining, remove the slag, let stand for 5~10 minutes, keep warm to 660°C, and obtain mixed melt 2;

[0049] (3) Preheat the iron mold to 210°C, and then pour the mixed melt 2 obtained in step (2) into the mold. Vacuum system is used to draw a vacuum (vacuum degree 10 kPa) for single-step die casting: the punch is advanced at a low speed of 0.1 m / s under a pressure of 90 MPa; after holding the pressure at 10 MPa for 10s, it solidifies, is demolded and cooled to obtain the alloy casting.

[0050] (4) Place the graphite electrode pairs tightly against both sides of the alloy casting obtained in step 3, and then perform high-frequency, oscillating, and cyclic current treatment with the following parameters: voltage 30V; current density 1×10⁻⁶. 7 A / m 2 The process was carried out at a frequency of 50Hz and a duty cycle of 20% for 0.5s. This process was repeated twice, and then the equipment was turned off. After the sample returned to room temperature, a die-cast aluminum-silicon alloy casting was obtained. In the obtained die-cast aluminum-silicon alloy casting, such as... Figure 4 As shown, the casting contains coarse, needle-like Fe-containing phases with a size of approximately 100 μm; Cu-containing phases in blocky form with a size of approximately 50 μm; α-Al grains with a coarse size of approximately 600 μm; and eutectic silicon phases in short rod-like forms with a size of 10 μm. The mechanical properties of the casting are: yield strength of approximately 158 MPa, tensile strength of approximately 260 MPa, and elongation after fracture of 8.1%.

[0051] The component ratio and process parameters used in each embodiment of the present application are different, and the properties and microstructure of the finally obtained alloy are also different, thus indicating that the optimal effect obtained by the present application is not determined by a certain component ratio or a certain process parameter, but is achieved by synergistic regulation of component interaction, ratio, process and process parameters (including melting temperature, die casting pressure and speed, and high-frequency-oscillation-cyclic current treatment parameters, etc.). Compared with Comparative Example 1, although the alloy components and processes used in the present application and Comparative Example 1 are similar, the component ratio and process parameters are not within the scope of the claims of the present application, and the yield strength of Comparative Example 1 is only 158 MPa, the tensile strength is 260 MPa, and the elongation after fracture is only 6.1%, which are all lower than the lowest performance of the alloy obtained by the present application. Therefore, only within the component interval and process parameter range defined in the claims of the present application, the optimal technical effect can be achieved. Compared with the prior art, the present application simultaneously greatly improves the comprehensive mechanical properties of the alloy, such as yield strength (≥26% higher than the prior art), tensile strength (≥20% higher than the prior art) and elongation after fracture (≥82% higher than the prior art). This synergistic improvement effect of "high strength and high plasticity" completely breaks through the technical bottleneck that the strength and plasticity of the prior art are difficult to balance. In addition, the present application breaks the multi-step addition of complex process and unstable modifiers and refiners in the prior art, simultaneously realizes the synchronous refinement and optimization of α-Al grains, eutectic silicon, and harmful iron-containing and copper-containing phases, simplifies the process and speeds up the reaction process, avoids the pore expansion and high energy consumption caused by traditional heat treatment, simplifies the production process, shortens the manufacturing cycle, and has relatively low equipment investment, which is suitable for industrial production. While meeting the overall improvement of macro-mechanical properties, the present application simultaneously realizes efficient, economical and environmentally friendly mass production, and provides a feasible solution for large-scale application of high-performance lightweight aluminum alloy in the automobile industry. The present application has significant advantages in automobile lightweighting, and the high strength and plasticity alloy obtained by the present application can be successfully applied to key components such as automobile body, chassis and engine support, which can effectively replace traditional heavy steel or low-performance aluminum alloy, and realize significant weight reduction of the components under the premise of ensuring structural safety and reliability. This weight reduction effect directly translates into improvement of automobile fuel efficiency and reduction of carbon emissions, which meets the global trend of green and sustainable development of the automobile industry.

[0052] Table 1: Alloy mechanical property statistics table of Examples 1-3 and Comparative Example 1

[0053]

Claims

1. A high-performance die-cast aluminum-silicon alloy for lightweight automotive components, characterized in that: The aluminum-silicon alloy comprises, by weight percentage, the following components: composition: Si: 9.0~12.0 wt.%, Cu: 0.5~1.0 wt.%, Mg: 0.50~0.60 wt.%, Fe: 0.10~0.15 wt.%, Mn: 0.15~0.20 wt.%, Cr: 0.10~0.20 wt.%, B: 0.03~0.06 wt.%, La: 0.10~0.15 wt.%, unavoidable impurities ≤0.1 wt.%, balance Al; the preparation method of the aluminum-silicon alloy includes the following steps: (1) According to the alloy composition ratio, after grinding to remove surface stains and oil stains, Al-Si, Al-Mn, Al-Cr, Al-Fe, Al-Cu, Al-B and Al-La alloy raw materials, heat them at 200~250℃ for 5~10 min; then heat them up to 750-780℃ for smelting; after the alloy melts, stir it evenly, then cool it down to 690~710℃, remove the slag, then add magnesium ingots to melt, stir evenly, and let it stand for 5~10 min to obtain mixed melt 1; The Al-Si alloy is any one of Al-10Si, Al-15Si, or Al-25Si alloys; the Al-Mn alloy is any one of Al-10Mn, Al-15Mn, or Al-25Mn alloys; the Al-Cr alloy is any one of Al-10Cr, Al-15Cr, or Al-25Cr alloys; the Al-Fe alloy is any one of Al-10Fe, Al-15Fe, or Al-25Fe alloys; the Al-Cu alloy is any one of Al-10Cu, Al-20Cu, Al-30Cu, or Al-50Cu alloys; the Al-B alloy is any one of Al-3B, Al-8B, or Al-10B alloys; and the Al-La alloy is any one of Al-5La, Al-10La, or Al-20La alloys. (2) After heating the mixed melt 1 obtained in step (1) to 720-750℃, remove slag, add refining agent, stir for 3-5 minutes, let stand for 5-10 minutes, then introduce high-purity argon gas for 3-5 minutes for degassing and impurity removal refining treatment, remove slag, let stand for 5-10 minutes, and then keep at 660-680℃ for 5-10 minutes to obtain mixed melt 2; the refining agent is K2CO3 or MgCO3, accounting for 0.2-0.6 wt.% of the total mass of mixed melt 2. (3) The mixed melt 2 obtained in step (2) is poured into an iron mold that has been preheated to 200~250℃, and then subjected to multi-stage high-pressure casting under vacuum conditions. The multi-stage high-pressure casting process is as follows: First stage: under pressure of 80~100MPa, the speed is 0.05~0.2 m / s; Second stage: under pressure of 100~120MPa, the speed is 0.5~1.5 m / s; Third stage: under pressure of 130~160MPa, the speed is 2-3 m / s; Fourth stage: under pressure of 10~20 MPa, the speed is 0.01~0.05 m / s; After holding the pressure at 5~10MPa for 10~15s, the mixture solidifies, is demolded, and cooled to obtain an alloy casting. (4) The alloy casting obtained in step (3) is subjected to high-frequency, oscillating, cyclic current treatment for 5 to 10 times. Each current treatment is performed with the following parameters: voltage 10 to 20V; current density 5×10⁻⁶. 7 ~3×10 9 A / m 2 ; The frequency is 20-30Hz; the duty cycle is 30-50%; the processing time is 1-2s, and then cooled to room temperature to obtain a high-performance die-cast aluminum-silicon alloy for lightweight automotive components; the high-performance die-cast aluminum-silicon alloy for lightweight automotive components has the following microstructure and properties: containing Al 15 (Fe, Mn, Cr)3Si2 and Cu-containing phases, with sizes ranging from 5 to 10 μm; α-Al grain size: 90 to 100 μm; eutectic silicon size: 1 to 5 μm; in terms of mechanical properties, its yield strength reaches ≥200 MPa, tensile strength reaches ≥300 MPa, and elongation after fracture reaches ≥15%.

2. The high-performance die-cast aluminum-silicon alloy for lightweight automotive components according to claim 1, characterized in that: The aluminum-silicon alloy comprises, by weight percentage, the following components: Composition: Si: 9.5~10.5 wt.%, Cu: 0.6~0.8 wt.%, Mg: 0.55~0.58 wt.%, Fe: 0.12~0.14 wt.%, Mn: 0.16~0.18 wt.%, Cr: 0.12~0.18 wt.%, B: 0.04~0.05 wt.%, La: 0.12~0.14 wt.%; unavoidable impurities ≤0.05 wt.%, balance Al.

3. The high-performance die-cast aluminum-silicon alloy for lightweight automotive components according to claim 1, characterized in that: In step (1), according to the alloy composition ratio, the Al-Si, Al-Mn, Al-Cr, Al-Fe, Al-Cu, Al-B and Al-La alloy raw materials are polished to remove surface stains and oil stains, and then kept at 220~240℃ for 6~8 min; then the temperature is raised to 760~770℃ for smelting; after the alloy melts, it is stirred evenly, then the temperature is lowered to 695~700℃, slag is removed, and then magnesium ingots are added to melt, stirred evenly, and kept at a constant temperature for 6~8 min to obtain mixed melt 1.

4. The high-performance die-cast aluminum-silicon alloy for lightweight automotive components according to claim 1, characterized in that: The refining agent mentioned in step (2) is K2CO3 or MgCO3, accounting for 0.3~0.5 wt.% of the total mass of the melt.

5. The high-performance die-cast aluminum-silicon alloy for lightweight automotive components according to claim 1, characterized in that: The mixed melt 2 obtained in step (2) is poured into an iron mold that has been preheated to 220~240℃, and then subjected to multi-stage high-pressure casting under vacuum conditions. The multi-stage high-pressure casting process consists of the following stages: first stage: under pressure of 85~95 MPa, the casting is advanced at a speed of 0.1~0.15 m / s; second stage: under pressure of 105~115 MPa, the casting is advanced at a speed of 0.8~1.2 m / s; third stage: under pressure of 140~150 MPa, the casting is advanced at a speed of 2.2~2.5 m / s; fourth stage: under pressure of 12~15 MPa, the casting is advanced at a speed of 0.02~0.04 m / s; after holding the pressure at 5~10 MPa for 12~14s, the casting solidifies, is demolded, and cooled to obtain the alloy casting.

6. The high-performance die-cast aluminum-silicon alloy for lightweight automotive components according to claim 1, characterized in that: The alloy casting described in step (4) is subjected to high-frequency, oscillating, 6-8 cycles of current treatment. Each current treatment is performed with a voltage of 15-18V and a current density of 8×10⁻⁶. 7 ~2×10 9 A / m 2 The frequency is 22~28Hz; the high-performance die-cast aluminum-silicon alloy of the aforementioned lightweight automotive components has the following microstructure and properties: containing Al 15 (Fe, Mn, Cr)3Si2 and Cu-containing phases, both with a size of 6~8 μm, α-Al grain size: 92~98 μm, eutectic silicon size: 2~4 μm; in terms of mechanical properties, its yield strength reaches ≥210MPa, tensile strength reaches ≥320MPa, and elongation after fracture reaches ≥16%.

Citation Information

Patent Citations

  • Machining method for improving mechanical property of aluminum alloy motor enclosure

    CN107470579A

  • Die-casting aluminum alloy preparation method based on aluminum-containing waste, die-casting aluminum alloy and application of die-casting aluminum alloy

    CN119320895A